Nicotinic acetylcholine receptor-mediated effects of varenicline on LPS-elevated prostaglandin and cyclooxygenase levels in RAW 264.7 macrophages - Baris, Elif; Arici, Mualla Aylin; Tosun, Metiner (Frontiers in Molecular Biosciences, 2024)
The purpose of this study is to delineate anti-inflammatory and anti-oxidant effectiveness of varenicline, a cigarette smoking cessation aid, on decreasing lipopolysaccharide (LPS)-elevated proinflammatory cytokines in RAW 264.7 murine macrophage cultures which we showed earlier to occur via cholinergic anti-inflammatory pathway (CAP) activation. In this study, we investigated whether varenicline suppresses LPS-regulated cyclooxygenase (COX-1 and COX-2) through α7 nicotinic acetylcholine receptor (α7nAChR) activation in an in vitro murine macrophage inflammation model, thereby reducing prostaglandin and reactive oxygen species (ROS) levels.We further investigated the contribution of nAChR subtypes by using non-selective and/or selective α7nAChR antagonists. COX-1, COX-2, PGE2, 6-keto prostaglandin F1α (a PGI2 metabolite) and thromboxane A2 (TxA2) levels were also measured by employing ELISA and the results were compared with conventional anti-inflammatory medications, such as ibuprofen, celecoxib and dexamethasone. The results showed that varenicline significantly reduced LPSinduced COX and prostaglandin levels, similar to that of ibuprofen, celecoxib, and dexamethasone, also decreasing ROS, suggesting varenicline's anti-inflammatory and antioxidant potential mediated partly by α7nAChRs.